2019
DOI: 10.1021/jacs.9b01857
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt-Catalyzed Intermolecular Hydrofunctionalization of Alkenes: Evidence for a Bimetallic Pathway

Abstract: A functional group tolerant cobalt-catalyzed method for the intermolecular hydrofunctionalization of alkenes with oxygen- and nitrogen-based nucleophiles is reported. This protocol features a strategic use of hypervalent iodine­(III) reagents that enables a mechanistic shift from conventional cobalt–hydride catalysis. Key evidence was found supporting a unique bimetallic-mediated rate-limiting step involving two distinct cobalt­(III) species, from which a new carbon–heteroatom bond is formed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
76
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(79 citation statements)
references
References 69 publications
2
76
0
1
Order By: Relevance
“…Recent studies on the (salen)Co-catalyzed hydrofunctionalization of alkenes with hypervalent iodine(III) carboxylates is consistent with an OLT or an RPC pathway that leads to product (Scheme 15). 124 Selectivity for hydrofunctionalization over isomerization was found to be sensitive to both concentration and enantioenrichment of the catalyst, implying that hydrofunctionalization involves the interaction of multiple cobalt species. Further kinetic analysis showed that formation of isomerization byproducts had a rst order dependence on [Co], whereas formation of hydrofunctionalized products had a second order dependence on [Co], suggesting that the turnover limiting step is a reaction between two distinct cobalt speciesan organocobalt complex and a cobalt-bound nucleophile.…”
Section: Alkyl Radical Trapping and Turnovermentioning
confidence: 98%
“…Recent studies on the (salen)Co-catalyzed hydrofunctionalization of alkenes with hypervalent iodine(III) carboxylates is consistent with an OLT or an RPC pathway that leads to product (Scheme 15). 124 Selectivity for hydrofunctionalization over isomerization was found to be sensitive to both concentration and enantioenrichment of the catalyst, implying that hydrofunctionalization involves the interaction of multiple cobalt species. Further kinetic analysis showed that formation of isomerization byproducts had a rst order dependence on [Co], whereas formation of hydrofunctionalized products had a second order dependence on [Co], suggesting that the turnover limiting step is a reaction between two distinct cobalt speciesan organocobalt complex and a cobalt-bound nucleophile.…”
Section: Alkyl Radical Trapping and Turnovermentioning
confidence: 98%
“…Very recently, Zhu and coworkers have proposed a unique bimetallic pathway for the Co(II)‐salen‐catalyzed hydrooxycarbonylation of alkenes using hypervalent iodine(III) reagents (Scheme ) . The treatment of alkene with iodine(III) reagent 71 and (Me 2 SiH) 2 O in the presence of Co(II)‐salen catalyst 72 afforded hydrooxycarboxylated product 73 in good yield.…”
Section: Planar Co(iii)‐hydride Complexesmentioning
confidence: 99%
“…2b) 20 source to form oximes 21 . Since Mukaiyama and coworkers 22 reported the iron-catalyzed hydroamination of unactivated alkenes via HAT, using phenyl silane as a reductant and butyl nitrite as an aminating reagent, various aminating reagents, such as azo compounds [23][24][25][26] , nitro compounds 27,28 , diazo compounds 29 , azides 24,30 , and amides 31,32 have been explored by many research groups, which offers a great opportunity for retrosynthetic possibility of new transformations. Although simple 1,3-dicarbonyl metal complexes could promote the reactions, stoichiometric amount or high loading of these complexes used to be necessary 20,33 .…”
mentioning
confidence: 99%